Stock Price Bubble, Debt Maturity Structur, Institusional Ownership dan Stock Price Crash Risk di Perusahaan Teknologi Indonesia - Megawati Sukarni Putri; Mohammad Fany Alfarisi; Rida Rahim (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This study aims to impirically determine the influence of the stock price bubble, long-term debt and institutional ownership on the stock price crash risk in Indonesian technology companies in 2019-2021. The sampling technique in this study was using the proposive sampling method and obtained samples of 16 companies with a total observation of 48. The data analysis used in this study used the panel data regression method using the eviews 10 analysis tool. The results of this study show that long-term debt has a significant effect on stock price crash risk, meaning that companies that have a larger long-term debt structure in their capital structure have a higher stock price crash risk. Meanwhile, the stock price bubble and institutional ownership do not have a significant effect on the stock price crash risk. Simultaneously or together the stock price bubble, long-term debt and institutional ownership have a significant effect on stock price crash risk. Based on the results of the coefficient determination test, an adjusted R-square value of 0.8497 was obtained, meaning that the contribution of the independent variable in explaining the dependent stock price crash risk variable was 84.97%. This research is expected to be used as a consideration for interested parties, especially company managers and investors, to be able to pay attention to the factors that will cause stock price crash risk in Indonesian technology companies.